2020
DOI: 10.5194/egusphere-egu2020-2760
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Denitrification induced by plant residues is driven by water-soluble organic carbon

Abstract: <p>Denitrification usually takes place under anoxic conditions and over short periods of time and depends on readily available nitrate and carbon sources. Variations in CO<sub>2</sub> and N<sub>2</sub>O emissions from soils amended with plant residues have mainly been explained by differences in their decomposability. Another factor rarely considered so far is water-extractable organic matter (WEOM) released into soil during residue decompos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In a recent study, Surey et al. [ 12 ] reported that WSOM from plant residues stimulated N 2 O emissions during initial decomposition. Therefore, the abundant WSOM from manure is expected to increase microbial activity and N 2 O emission from plastic greenhouse soil.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Surey et al. [ 12 ] reported that WSOM from plant residues stimulated N 2 O emissions during initial decomposition. Therefore, the abundant WSOM from manure is expected to increase microbial activity and N 2 O emission from plastic greenhouse soil.…”
Section: Introductionmentioning
confidence: 99%